Case Report: A Novel Point Mutation of SOX3 in a Subject With Growth Hormone Deficiency, Hypogonadotrophic Hypogonadism, and Borderline Intellectual Disability - Li, Jing; Zhong, Yuxia; Guo, Tao; Yu, Yerong; Li, Jianwei (Frontiers in Endocrinology, 2022)
SOX3 is critical for the development of pituitary, brain and face, and SOX3 mutations may lead to hypopituitarism, intellectual disability and craniofacial abnormalities. Common SOX3 mutations are duplications and deletions of the whole or part of SOX3, yet only a few cases with point mutations were reported by far. We presented a case with growth retardation, small penis, and learning difficulty. Further assessment confirmed growth hormone deficiency, hypogonadotrophic hypogonadism (HH), and borderline intellectual disability. He also responded well to gonadotropin-releasing hormone stimulation test, which suggests defects in the hypothalamus, contrary to the previous studies that reported defects in the pituitary. A pathogenic frame-shift mutation of SOX3 was found. A heterogeneous missense mutation in SEMA3A was identified in this patient as well, which may also contribute to the development of HH. As far as we know, this is the first report that a frame-shift mutation of SOX3 constitutes rare genetic causes of hypogonadotrophic hypogonadism and growth hormone deficiency. Whether mutations in these two genes act synergistically in the pathogenesis of his phenotype remains further investigation. We believe that our case extends the phenotypic spectrum and genetic variability of SOX3 mutation.